HACKER ATTACKS UNDETECTABLE ATTACKS FROM TROJANS WITH REVERSE COMMUNICATION - Piperevski, Mane (Matematichki Bilten, 2015)
Computer integration in everyday human life create a motive for developing sophisticated and undetectable malicious codes, Trojans with reverse communication that make use of deficiencies and vulnerability in the chain of security.